Nilai-Nilai Sosial Tari Pilin Salapan di Kenagarian Air Bangis Kecamatan Sungai Beremas Kabupaten Pasaman Barat - Vitania Averin; Darmawati Darmawati (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
This study aims to reveal and describe social values in Pilin Salapan Dance in Nagari Air Bangis, Sungai Beremas District, West Pasaman Regency. The type of research used in this study is qualitative research. The data type uses primary data and secondary data. The main instrument in this study was the researcher himself and was assisted by supporting instruments such as stationery and cameras. Data collection techniques are carried out by means of literature studies, observations and documentation. The steps of analyzing data are collecting data, describing the data and inferring the data. The results showed that Pilin Salapan Dance grew and developed in the Kanagarian Air Bangis sub-district of Sungai Beremas, West Pasaman Regency. The social values contained in the Pilin Salapan Dance are the values of struggle that are seen when dancers play wooden props as a symbol of weapons for young people, music as adding to the spirit of the dancers, strands of cloth that are woven as a symbol of the cohesiveness of the dancers because when slipping the ropes must be compact and spirited. The social values contained in the Pilin Salapan Dance are: 1) the social value of compassion which consists of the social value of devotion, the social value of family, the social value of helping, the social value of loyalty and the social value of caring, 2) the social value of responsibility, 3) the social value of harmony in life, which consists of the social value of cooperation and the social value of tolerance.